Relevance and quality of the Gipuzkoan extracurricular youth sports program: an evaluation from a positive youth development perspective - Zubizarreta, Ekain; Ortuondo, Jon; Usabiaga, Oidui; Martinez-Merino, Nagore (Frontiers in Psychology, 2024)
Physical activity and sport (PAS) programmes are an important part of organised extracurricular activities for children and young people. They appear as potentially inclusive environments where students could be provided with holistic development based on active and healthy lifestyles. The aim of this study was to evaluate and describe the Gipuzkoa School Sport Programme (GSSP) from the Positive Youth Development (PYD) perspective, using Tejedor's (2000) guidelines of programme evaluation. The research was carried out based on CPAR (Critical Participatory Action-Research) methodology: a 'CPAR group' was created -including researchers and policymakers-to carry out the evaluation of the GSSP in which we analysed a) the social environment or PYD climate and b) life skills (Holt et al., 2017). The evaluation and description of the GSSP confirmed that it meets most requirements for providing positive development contexts and opportunities for PYD. The choice of prioritising multisport and deliberate play and putting early specialisation aside seem key conditions to ensure PYD-promoting environments. This work could serve as a referent for decisionmakers in organisations dedicated to designing, developing, implementing, and evaluating PYDfocused extracurricular youth sport programmes.